COMUNICACIÓN INTRAFAMILIAR Y SU INFLUENCIA EN LA CONDUCTA DE LOS NIÑOS Y JOVENES DEL CANTÓN EL EMPALME DE LA COOPERATIVA ATILIO VÉLEZ ARAY. AÑO 2022. - Loor Alava, Tiylor Fernando (2022)
The objective of this research is to identify the influence of intrafamily communication in the behavior of children and young people of the canton El Empalme of the cooperative Atilio Vélez Aray. The modality of the research is of mixed type, the analytical, inductive and deductive methods were used, also the survey technique was applied with an instrument of eight questions of multiple options applied to the children and young people of this locality. Obtaining as results the types of families to which these people belong, the type of communication used in their homes, the language used, the frequency with which they consider that there is intrafamily communication in their homes, also it was identified if these children and young people communicate to the members of their homes thoughts, feelings, fears or emotions and if in these families the opinions of the other members of the home are respected, therefore to know the type of behavior that these young people present and finally to know how is their behavior with other people. All this on the basis of identifying the influence of intrafamily communication in the behavior of children and young people of the canton El Empalme of the cooperative Atilio Vélez Aray.